Flumequine, a fluoroquinolone in disguise - Aram F. Swinkels; Egil A. J. Fischer; Lisa Korving; Rafaella Christodoulou; Jaap A. Wagenaar; Aldert L. Zomer (npj Antimicrobials and Resistance, 2024)
Abstract Fluoroquinolone resistance in E. coli isolates from livestock in Europe remains high despite EMA restrictions on fluoroquinolone use in animals. However, flumequine, a quinolone not classified as a fluoroquinolone by various regulatory bodies, is still used in livestock in the Netherlands, Belgium, Greece and France. We investigated whether flumequine selects for the same resistance mechanisms in E. coli. Resistant and non-resistant E. coli isolates were obtained from caecal fermentation assays and broilers exposed to concentrations of flumequine and enrofloxacin. Flumequine usage leads to an approximately 3-fold increase in resistant E. coli in the caecal fermentation, similar to enrofloxacin. In vitro exposure to both flumequine and enrofloxacin revealed the same amino acid substitutions (S83L, D87G) in GyrA. Additionally, the same resistance-causing substitutions were found in phenotypically resistant E. coli isolates from broilers treated with either enrofloxacin or flumequine. Flumequine induces similar resistance mechanisms as enrofloxacin, warranting equivalent restrictions on its use.